The art of Fire emblem, awakening - Flanagan, William (Milwaukie, Or. : Dark Horse Books, 2016)
"The Art of Fire Emblem Awakening contains an in-depth, behind-the-scenes look at the smash-hit 3DS game, from beautifully illustrated renditions of your favorite characters, to storyboards for in-game events, character designs, weapon designs, character profiles, and the entirety of the script with every possible branch of dialogue! Relive some of the most poignant moments of the game, or see what might have been if you had made different in-game decisions with the Art of Fire Emblem Awakening!"--
""An in-depth, behind-the-scenes look at the smash-hit Nintendo game"--Provided by publisher"--
"All concept illustrations that originally contained handwritten notes in Japanese have been translated into English and updated for this version of the book."
Keywords: Video games -- Pictorial works. -- Design; Video games in art